Systemic administration of imiquimod as an adjuvant improves immunogenicity of a tumor-lysate vaccine inducing the rejection of a highly aggressive T-cell lymphoma - Di Sciullo, Maria Paula; Menay, Florencia; Cocozza, Federico; Gravisaco, María José; Waldner, Claudia Inés; Mongini, Claudia (Elsevier, 2019)
T-cell lymphomas include diverse malignancies. They are rare, some have low survival rates and they lack curative therapies. The aim of this work was to assess whether employing the TLR7 agonist imiquimod and the T-cell costimulatory molecule CD40 or the combination of both as adjuvants of a cell lysate vaccine could enhance the antitumor immune response using a murine T-cell lymphoma model. Immunization with LBC-lysate and imiquimod protected almost all vaccinated animals. A specific humoral and a Th1-type cellular immunity were induced in mice that rejected the lymphoma, characterized by an elevated number of CD4 + T-cells and secretion of IFN-γ, locally and systemically. In contrast, CD40 alone or in combination with imiquimod did not improve the protective response obtained with LBC-lysate and imiquimod. Systemic administration of imiquimod proved to have high potential to serve as a vaccine adjuvant for the treatment of T-cell lymphomas and was effective in this immunotherapy model.